2014
DOI: 10.5539/jel.v3n4p37
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Teachers’ Perceptions of Improving Critical Thinking Skills in Saudi Arabian Elementary Schools

Abstract: The intent of this explanatory sequential mixed-method study is to examine Islamic teachers' thoughts on improving critical thinking skills in elementary schools in the Southwestern province of Saudi Arabia. This study involves the collection of quantitative data and an explanation of the quantitative results with qualitative data. In the first phase, a survey was administered to Islamic teachers in Saudi elementary schools to assess their opinions on improving students' critical thinking skills and to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 51 publications
12
38
0
1
Order By: Relevance
“…This study found that lack of time and readiness is confirmed to be a barrier when using critical thinking abilities incorporated to students' constructive learning. This finding is consistent with Alazzi (2008) and Alwadai (2014) research show that students may think critically with their own mental ability, but enhancing the ability of critical reasoning requires time, strategies and motives guided by teachers. According to Alwadai (2014) time is a significant obstacle in developing skills in critical thinking in large classrooms.…”
Section: Results For Second Research Questionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study found that lack of time and readiness is confirmed to be a barrier when using critical thinking abilities incorporated to students' constructive learning. This finding is consistent with Alazzi (2008) and Alwadai (2014) research show that students may think critically with their own mental ability, but enhancing the ability of critical reasoning requires time, strategies and motives guided by teachers. According to Alwadai (2014) time is a significant obstacle in developing skills in critical thinking in large classrooms.…”
Section: Results For Second Research Questionsupporting
confidence: 90%
“…This finding is consistent with Alazzi (2008) and Alwadai (2014) research show that students may think critically with their own mental ability, but enhancing the ability of critical reasoning requires time, strategies and motives guided by teachers. According to Alwadai (2014) time is a significant obstacle in developing skills in critical thinking in large classrooms. They also found that teachers strive to provide students with knowledge in the specific field but experience time challenges with lack of useful learning tools to teach students critical thought.…”
Section: Results For Second Research Questionsupporting
confidence: 90%
See 1 more Smart Citation
“…Research conducted by Aktas & Unlu, concluded that the critical thinking skills of the basic mathematics preservice teacher are at the middle level but not high enough level [6]. Research conducted by Alwadai, concluded that prospective teachers find the biggest obstacle in improving students' critical thinking skills is the ability of students themselves [7]. The research by Applebaum & Mark concluded that prospective teachers found it difficult to develop critical thinking skills because of difficulties in analyzing the probability of mistakes and overcoming the students' mental incompatibility when faced with opposing answers to geometry [8].…”
Section: Introductionmentioning
confidence: 99%
“…Alaqeel (2013) establishes that helping students think critically and develop their skills in observation and analysis is one of the main aims of secondary school education. Although there are studies conducted in Saudi Arabia that acknowledge the importance of teaching students critical thinking skills and training teachers to implement strategies to attain this goal (Alghamdi et al, 2013;Allamnakhrah, 2013;Alwadai, 2014), there are still very few studies that aimed to investigate effective and useful teaching practices that may promote the development of learners' critical thinking skills. The findings of this study may help teachers to decide on the most useful teaching practices to enable the development of critical thinking skills and positively affect students' learning.…”
Section: Introductionmentioning
confidence: 99%